Potentially fluorescent ligands based on the N,N-dialkyl-N’- aroylthiourea motif and their Pt(II) and Pd(II) complexes. - Bruce, Jocelyn (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2005.